Estudo in vitro de ações biológicas da ficocianina livre e microencapsulada - Dias, Thanise Antunes (2021)
The search for alternative therapies has increased the use of bioactive compounds in the food and nutraceutical industry. Phycocyanin is a bioactive compound with antioxidant, antiinflammatory, hepatoprotective, anti-cancer potential, among others. However, its low stability in terms of luminosity, temperature and acidity limits its application. Microencapsulation is a technique used to preserve bioactive compounds and increase their bioavailability. This study aimed to evaluate the core:wall material ratio on the bioavailability of phycocyanin and its anti-inflammatory action in vitro. Phycocyanin was microencapsulated in the proportions 0.75% and 1%, through ionic gelation, using sodium alginate as wall material in the proportions 1% and 1.5%. The capsules were evaluated for morphology, encapsulation efficiency (EE), functional groups, thermal stability, release profile in simulation of the digestive system (acidic and basic pHs) in addition to the antioxidant and anti-inflammatory profile. The core:wall material ratio did not significantly influence the EE. The increase in sodium alginate caused an increase in the water solubility of the capsules, however, the increase in the concentration of phycocyanins resulted in a decrease. In addition, phycocyanin microencapsulation promoted the conservation of antioxidant stability during storage, in the form of microcapsules (5 weeks). The microencapsulated phycocyanin showed inhibition of protein denaturation of 95.96%, protease inhibition of 72.5%, inhibition of hemolysis induced by hypotonic solution and heat of 96.64% and 96.56%, respectively. In general, the microcapsules showed thermal and stomach pH resistance, enabling the release of phycocyanin at intestinal pH, ensuring its bioavailability and preserving its functional properties. Therefore, the microencapsulated phycocyanin showed potential to reduce the expression of pro-inflammatory cytokines.